Occupancy dynamics of semi‐aquatic herbivores in riparian systems in Illinois, USA. Issue 3 (6th March 2019) - Holland, Angela M.; Schauber, Eric M.; Nielsen, Clayton K.; Hellgren, Eric C.
Abstract: Streams and local riparian habitats are a product of the landscapes they drain. Consequently, aspects of the landscape, as well as local stream morphology, are likely to affect riparian and stream communities, including occupancy of semi‐aquatic mammals. To gain a better understanding of how changing landscapes may affect the occupancy of semi‐aquatic mammals, we sought to identify aspects of the riparian system and stream structure at multiple scales that relate to the presence of beaver ( Castor canadensis ) and muskrat ( Ondatra zibethicus ), including their interactions with mink ( Neovison vison ) and river otter ( Lontra canadensis ). We estimated multi‐season occupancy using 103 sites sampled over six seasons (2012–2014) in southern Illinois, USA. We hypothesized beaver and muskrat occupancy was related to multiple aspects of landscape and local habitat including land‐cover, water availability, human disturbance, stream characteristics, and the presence of other semi‐aquatic mammals. Beaver occupancy varied over time and was predicted by stream size, stream density, and land‐cover at the landscape scale. Muskrat occupancy also varied over time and was related to local aspects of habitat including percentage of forest in the riparian area, channel incision, land‐cover, and aspects of sediment chemistry. Our results indicate the importance of spatial and temporal variation, scale, and food and water availability for these semi‐aquatic species. Beaver and muskrat are most likely to be affected by changes to water regimes including availability of permanent water sources due to changing landscapes.